Penerapan Model Pembelajaran Kooperatif Tipe Cooperative Integrated Reading And Composition (CIRC) Berbantuan Media Audio Visual Untuk Meningkatkan Hasil Belajar Geografi Siswa Kelas XI SMA Negeri 1 Setia Bakti Aceh Jaya - Elviana, Meri; Desfandi, Mirza; Furqan, Muhammad Hafizul (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2024)
This study aims to determine the effectiveness of implementing the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by audiovisual media in improving the learning outcomes of eleventh-grade social science students at SMA Negeri 1 Setia Bakti, Aceh Jaya. Based on initial observations, learning at this school remained conventional, requiring a more interactive approach. The CIRC model was applied to encourage students to be more active in reading and writing, thereby enhancing their understanding of the material. This study employed a classroom action research (CAR) method with three cycles. The research subjects were 21 eleventh-grade social science students. Data were collected through pre-tests and post-tests, observations of teacher and student activities, assessments of teachers' teaching skills, and student response questionnaires. Data analysis was conducted using descriptive percentage statistics.The results showed an improvement in students learning outcomes, with individual mastery increasing from 43% in cycle I to 76% in cycle II and 91% in cycle III. Classical mastery also increased from 50% in cycle I to 70% in cycle II and 90% in cycle III. Teacher and student activities increased from 8 activities in cycle I to 12 activities in cycle II and 14 activities in cycle III. The teachers teaching skills improved from a moderate category (2.50) in cycle I to good (3.21) in cycle II and very good (3.54) in cycle III. A total of 90.5% of students responded positively to the CIRC model assisted by audiovisual media, as it was considered enjoyable and facilitated material comprehension.